Breast cancer patients presenting with cardiotoxicity - risk factors and role of cardioprotective drugs. (4th February 2022) - Martins De Carvalho, M; Proenca, T; Pinto, RA; Costa, I; Torres, S; Resende, CX; Grilo, PD; Amador, AF; Costa, C; Calvao, J; Cabrita, A; Marques, C; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Recent advances in cancer treatment have led to improved survival, albeit with cardiovascular adverse effects being some of the most frequent and feared consequences. Patient's risk stratification, prevention and treatment are still to be fully elucidated. Our aim was to evaluate the risk and therapy of cardiotoxicity (CT) secondary to cancer treatment in a subset of patients with breast cancer (BC). Methods: We collected a retrospective cohort of female with BC treated with conventional chemotherapy (CHT) and/or anti-HER2-targeted therapies (AHT) referred to Cardio-oncology consultation from January 2017 to March 2020. All patients were evaluated before CHT and at least at 3, 6 and 12-months with echocardiogram and cardiac biomarkers, namely high sensitivity troponin I (hs-cTnI) and brain natriuretic peptide (BNP). CT was defined as left ventricle ejection fraction (LVEF) under 50% or decline of at least 10% in LVEF during follow-up. As cardioprotective drugs (CPD) we considered renin-angiotensin-aldosterone system inhibitors and beta-blockers. Results: A total of 203 women were enrolled, with mean age 50.9 ± 10.9 year-old. As for the cardiovascular risk factors, 23.5% had hypertension, 32.4% dyslipidaemia, 9.8% diabetes and 33.0% were smokers or previous smokers. The majority of patients had a high or very-high CT risk score (98.5% with score ≥ 5) and 35.5% were already on CPD before CHT. All patients were submitted to CHT: anthracyclines (AC) and AHT were applied to 83.8% and 41.7% of patients, respectively, with 27.9% of patients on both therapies; 81.4% were submitted to radiotherapy (RT). At presentation, all patients had normal cardiac function with mean LVEF of 62.9% and mean global longitudinal strain (GLS) of -19.4; mean hs-cTnI and BNP were 3.3 ng/L and 33.4 pg/mL, respectively. During a median follow-up of 16 months, 8.5% of patients developed CT, leading to initiation or titration of CPD in 76.9% and treatment interruption in 23.5%; most of them recovered (88.2%). During treatment there was a significantly increase of hs-cTnI (mean 19.7 ng/L at 3 months, p < 0.001) and a decrease of GLS and LVEF at 12 months (decrease of 1.1 and 2.2%, respectively, both p < 0.001). Both AHT and AHT plus AC were significantly associated with CT (p = 0.002 and p < 0.001, respectively), with an extremely high prevalence in the latter group (19.6%). Nor CVRF neither RT raised the risk of CT. Although patients on CPD did not had lower prevalence of CT (5.6% vs 10.2%, p = 0.268), its initiation was associated with a higher rate of cardiac function recovery (100.0% vs 66.7%, p = 0.057). Conclusion: Patients submitted to AHT or AHT plus AC were at higher risk of developing CT. This and the significant LVEF decline during follow-up highlight the importance of long-term-monitoring of these patients. CPD seemed to be associated with cardiac recovery, although this finding needs further validation.